Preoperative serum placenta growth factor level as a new marker for stage II or III colorectal cancer patients - Özgür KEMİK,; Ahu Sarbay Kemik,; Aziz SÜMER,; Sevim PURİSA,; Barış TÜKENMEZ,; Sefa TÜZÜN, (Turkish Journal of Gastroenterology, 2019)
-